Vestibular Evoked Myogenic Potential (VEMP) Testing for Diagnosis of Superior Semicircular Canal Dehiscence - Noij, Kimberley S.; Rauch, Steven D. (Frontiers in Neurology, 2020)
Superior semicircular canal dehiscence is a bony defect of the superior semicircular canal, which can lead to a variety of auditory and vestibular symptoms. The diagnosis of superior semicircular canal dehiscence (SCD) can be challenging, time consuming, and costly. The clinical presentation of SCD patients resembles that of other otologic disease, necessitating objective diagnostics. Although temporal bone CT imaging provides excellent sensitivity for SCD detection, it lacks specificity. Because the treatment of SCD is surgical, it is crucial to use a highly specific test to confirm the diagnosis and avoid false positives and subsequent unnecessary surgery. This review provides an update on recent improvements in vestibular evoked myogenic potential (VEMP) testing for SCD diagnosis. Combining audiometric and conventional cervical VEMP results improves SCD diagnostic accuracy. High frequency VEMP testing is superior to all other methods described to date. It is highly specific for the detection of SCD and may be used to guide decision-making regarding the need for subsequent CT imaging. This algorithmic sequential use of testing can substantially reduce radiation exposure as well as cost associated with SCD diagnosis.